2010
DOI: 10.1074/jbc.m110.130435
|View full text |Cite
|
Sign up to set email alerts
|

Role of H-1 and H-2 Subunits of Soybean Seed Ferritin in Oxidative Deposition of Iron in Protein

Abstract: Naturally occurring phytoferritin is a heteropolymer consisting of two different H-type subunits, H-1 and H-2. Prior to this study, however, the function of the two subunits in oxidative deposition of iron in ferritin was unknown. The data show that, upon aerobic addition of 48 -200 Fe 2؉ /shell to apoferritin, iron oxidation occurs only at the diiron ferroxidase center of recombinant H1 (rH-1). In addition to the diiron ferroxidase mechanism, such oxidation is catalyzed by the extension peptide (a specific do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…The present work actually showed that soybean ferritins protected ccc1⌬ yeast cells from iron toxicity, despite previous studies that used human ferritins not being able to show a protective effect when expressed in a ccc1⌬ strain (63). Previous in vitro studies reported that SFerH1/SFerH2 heteropolymers display greater iron oxidation activity and DNA protection from oxidative damage during iron oxidative deposition than soybean ferritin homopolymers (30,64). Here, it was observed that simultaneously expressed SFerH1 and SFerH2 assembled into heteropolymers in yeast.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…The present work actually showed that soybean ferritins protected ccc1⌬ yeast cells from iron toxicity, despite previous studies that used human ferritins not being able to show a protective effect when expressed in a ccc1⌬ strain (63). Previous in vitro studies reported that SFerH1/SFerH2 heteropolymers display greater iron oxidation activity and DNA protection from oxidative damage during iron oxidative deposition than soybean ferritin homopolymers (30,64). Here, it was observed that simultaneously expressed SFerH1 and SFerH2 assembled into heteropolymers in yeast.…”
Section: Discussioncontrasting
confidence: 45%
“…However, in pea seeds, Ͼ90% of iron is stored in phytoferritin, which is required for plant germination and early growth (27,28). In vitro work has shown that the SFerH1 and SFerH2 subunits synergistically interact during iron mineralization by exhibiting greater iron oxidation activity than separate homopolymers (29,30). Soybean ferritin has been used to enrich cereals with iron (31)(32)(33).…”
mentioning
confidence: 99%
“…So far, the amino acids involved in the definition of the ferroxidase center are highly conserved in all reported plant ferritins, but these ferritins are different in the catalyzing activity with each other, suggesting that amino acid residues nearby the ferroxidase centers or other amino acids have an effect on such activity. Consistent with this idea, our recent studies found that recombinant H-1 soybean seed ferritin (rH-1) exhibited a stronger catalytic activity than recombinant H-2 soybean seed ferritin (rH-2), although their ferroxidase centers are identical (Deng, Liao, Yang, Zhang, Hua, Masuda, Goto, Yoshihara, & Zhao, 2010). Another possible reason for the large difference in the catalytic activity between BBSF and PSF is stemmed from their different subunit composition (Fig.…”
Section: Fe 2 + Oxidative Deposition In Proteinmentioning
confidence: 71%
“…5). Agreeing with this view, it was observed that, at low iron loading of protein (48 Fe 2 + /protein shell), rH-1 exhibited a stronger iron oxidation activity than its analogs, rH-2, which was attributed to the larger catalytic ability of the ferroxidase centers within H-1 subunit than those in H-2 (Deng, Liao, Yang, Zhang, Hua, Masuda, Goto, Yoshihara, & Zhao, 2010). BBSF contains more H-2 subunits than PSF, so this might be an important reason why it exhibits a slower kinetics as compared to PSF.…”
Section: Fe 2 + Oxidative Deposition In Proteinmentioning
confidence: 80%
See 1 more Smart Citation